2013
DOI: 10.1111/j.1469-0691.2012.03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremic nosocomial pneumonia caused by Acinetobacter baumannii and Acinetobacter nosocomialis: a single or two distinct clinical entities?

Abstract: The phenotypically indistinguishable Acinetobacter baumannii and Acinetobacter nosocomialis have become leading pathogens causing nosocomial pneumonia in critically ill patients. A. baumannii and A. nosocomialis nosocomial pneumonias were grouped as a single clinical entity previously. This study aimed to determine whether they are the same or a different clinical entity. A total of 121 patients with A. baumannii and 131 with A. nosocomialis bacteremic nosocomial pneumonia were included during an 8-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Several studies have shown that these different species within the ACB complex exhibit unique epidemiologic niches, drug resistance patterns, and virulence characteristics within the nosocomial environment (9, 10). In addition, recent studies have demonstrated that patients infected with non-baumannii ACB complex bacteria have fewer comorbidities and improved clinical outcomes than patients with A. baumannii infections (7,(11)(12)(13). Thus, determining the species within the ACB complex that is responsible for an infection has important medical implications.…”
mentioning
confidence: 99%
“…Several studies have shown that these different species within the ACB complex exhibit unique epidemiologic niches, drug resistance patterns, and virulence characteristics within the nosocomial environment (9, 10). In addition, recent studies have demonstrated that patients infected with non-baumannii ACB complex bacteria have fewer comorbidities and improved clinical outcomes than patients with A. baumannii infections (7,(11)(12)(13). Thus, determining the species within the ACB complex that is responsible for an infection has important medical implications.…”
mentioning
confidence: 99%
“…2 Species identification with commercial identification systems that are currently used in clinical microbiology laboratories remains problematic, and molecular methods have been developed and validated for identification of Acinetobacter species. 3 Given that A. baumannii, Acinetobacter genomic species 3, and Acinetobacter genomic species 13TU share important clinical and epidemiological characteristics, the need for species identification of the ACB complex in clinical microbiology laboratories is questionable. 3,4 Moreover, A. calcoaceticus is the environmental species that has frequently been recovered from soil and water, and the designation "ACB complex" may be misleading and not appropriate if used in a clinical context.…”
Section: Reply To Su and Chaomentioning
confidence: 99%
“…3 Given that A. baumannii, Acinetobacter genomic species 3, and Acinetobacter genomic species 13TU share important clinical and epidemiological characteristics, the need for species identification of the ACB complex in clinical microbiology laboratories is questionable. 3,4 Moreover, A. calcoaceticus is the environmental species that has frequently been recovered from soil and water, and the designation "ACB complex" may be misleading and not appropriate if used in a clinical context. 3 The majority of studies that have addressed epidemiological and clinical issues related to Acinetobacter, including ours, have not employed identification methods for the ACB complex.…”
Section: Reply To Su and Chaomentioning
confidence: 99%
See 2 more Smart Citations